Design of a Leadership and Inclusive Learning Poster to Support Artificial Intelligence Utilization - Selfiana Khoirunnisa; Oktaviana Purnamasari (Journal of Contemporary Pedagogy and Learning Science, 2026)
The rapid advancement of digital technology, particularly Artificial Intelligence (AI), has significantly transformed contemporary education, leadership, and communication systems. This study aims to describe the design process of the poster entitled “AI Shapes the Future of Education”, which was developed for the International Virtual Short Course (IVSC) 2025 Poster Competition under the subtheme Innovative Digital Tools for Leadership and Inclusive Learning and achieved Second Place at the international level. This research employs a descriptive qualitative approach through literature review and design process documentation. The findings reveal that the poster development involved several stages, including concept formulation, message construction, visual element selection, typography and color determination, and final artwork refinement. The poster integrates educational advertising principles, including headline, subline, and call-to-action, with graphic design elements representing the collaboration between humans and AI technology in creating inclusive, adaptive, and sustainable education. The study highlights that visual communication design can function as an effective medium for promoting AI literacy, digital leadership, and inclusive learning awareness. Participation in the international competition also contributed to developing students’ digital communication skills, visual creativity, and critical thinking while strengthening academic representation in global contexts.